Exploring career awareness and aspirations of Malaysian school children - Ismail, Khamsiah; Abd. Hamid, Siti Rafiah; Anuar, Maryam Naziifah; Mohamed, Saiful Redza; Wan Abdullah, Wan Ashmirullah (2014)
Abstract: This study aimed to examine reported career development of children in primary schools which comprises of three variables, which are educational aspiration, career aspiration and level of career awareness and also observed the difference of aspirations and career awareness across genders and school locations. It also investigated the relationship between their aspirations and career awareness. The research questions of this study were explored using two-scale career awareness inventory, comprising of Knowledge about Career Test (KaWT) and Job Awareness Test (JAT). Career aspiration and educational aspiration was assessed by self-developed items. Data collected from a sample size of 703 was analyzed using Statistical Package for the Social Sciences (SPSS). Four conclusions were drawn from this study: (a) significant relationships were found between career awareness and career as well as educational aspirations; (b) career aspiration was found to have significant positive association with educational aspiration; (c) significant difference was found between male and female children educational aspirations; (d) significant difference was found between career awareness of children in urban and rural schools. This study gave emphasis to the need for an early start of career development intervention for children in primary school. More research is needed to extend the breadth of findings regarding the relationships between the variables and development of career intervention strategies that suit the need of students in Malaysia educational settings.